Power production from excess heat in a district heating system - Winther, Jonathan (My University, 2018)
Göteborg Energi is contemplating whether excess heat in the district heating (DH)system of Gothenburg can be used to produce electrical power. An ORC solution for electric power production is sought and a handful of options are found. Through an elimination process only one solution remains; an ORC-based heat engine from the company ClimeOn. The heat from the cold side of the ORC machine is stored in a seasonal borehole thermal energy storage (BTES) system. The specifications of the district heating system such as temperatures and flow rates are collected and investigated as well as relevant weather data. A base case is set up as a reference case for comparing the results. A BTES is designed and simulated as well. The placement of the ORC machine within the district heating system of Gothenburg is determined and the power production is also calculated. A sensitivity analysis with different temperatures and flow rates is also carried out and presented. Five other cases are set up from the sensitivity analysis. A life cost analysis is done on all the cases. Three different electricity prices are investigated; 85 SEK/MWh (low), 282.5 SEK/MWh (mean) and 448.4 SEK/MWh (high). The results show that when operating seasonally between May-September the net present value (NPV) is not favourable. However, in Case 5 where an all-year operation is assumed, the NPV is positive if the electricity price is average or above average. A payback period of 10 and 28 years is achieved when considering a high and average electricity price respectively.
Keywords: Annan samhällsbyggnadsteknik; Hållbar utveckling; Energi; Innovation och entreprenörskap (nyttiggörande); Other Civil Engineering; Sustainable Development; Energy; Innovation & Entrepreneurship